2006
DOI: 10.1016/j.cell.2006.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Nef-Mediated Suppression of T Cell Activation Was Lost in a Lentiviral Lineage that Gave Rise to HIV-1

Abstract: High-level immune activation and T cell apoptosis represent a hallmark of HIV-1 infection that is absent from nonpathogenic SIV infections in natural primate hosts. The mechanisms causing these varying levels of immune activation are not understood. Here, we report that nef alleles from the great majority of primate lentiviruses, including HIV-2, downmodulate TCR-CD3 from infected T cells, thereby blocking their responsiveness to activation. In contrast, nef alleles from HIV-1 and a subset of closely related S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

33
500
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 362 publications
(535 citation statements)
references
References 47 publications
33
500
1
1
Order By: Relevance
“…However, the conservation of highly efficient TCR downregulation after progression shows that, in vivo, TCR downregulation does not preclude disease progression in HIV-2 infection. This contrasts with the observation that the loss of TCR downregulation by Nef seems to be the cause of CD4 depletion in sooty mangabeys (22). CD4 depletion in HIV-2 infection is associated with increased viral replication, with immune activation, and, finally, with immunodeficiency, which is not the case in SIVsmm infection (21,26).…”
Section: Vol 83 2009 Hiv-2 Nef Does Not Protect Against Disease Promentioning
confidence: 64%
See 3 more Smart Citations
“…However, the conservation of highly efficient TCR downregulation after progression shows that, in vivo, TCR downregulation does not preclude disease progression in HIV-2 infection. This contrasts with the observation that the loss of TCR downregulation by Nef seems to be the cause of CD4 depletion in sooty mangabeys (22). CD4 depletion in HIV-2 infection is associated with increased viral replication, with immune activation, and, finally, with immunodeficiency, which is not the case in SIVsmm infection (21,26).…”
Section: Vol 83 2009 Hiv-2 Nef Does Not Protect Against Disease Promentioning
confidence: 64%
“…It was recently shown that HIV-1 and its simian ancestor, SIVcpz, have one distinctive characteristic that may contribute to pathogenesis. In contrast to the Nef proteins of other immunodeficiency viruses, HIV-1 and SIVcpz Nef proteins are unable to downregulate the T-cell receptor (TCR) from the surfaces of infected cells (1,22). Schindler and colleagues proposed that TCR downregulation protects the host from the impact of chronic immune activation (22), which is increasingly thought to play a major role in HIV-1 disease progression (7).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, activation-induced cell death after TCR engagement runs the risk of limiting the life span of productively infected cells and thus the amount of viral progeny produced. Consequently, HIV-1 encodes gene products, such as Nef, to finetune activation states of infected T lymphocytes (15,16). Nef is a 25-to 34-kDa myristoylated accessory protein encoded by HIV-1, HIV-2, and SIV.…”
mentioning
confidence: 99%